2020
DOI: 10.1108/ecam-07-2020-0525
|View full text |Cite
|
Sign up to set email alerts
|

Identifying critical factors influencing the safety of Chinese subway construction projects

Abstract: PurposeThe image of the construction industry in China, as in many other countries, is tarnished by its poor safety record. With the rapid development of subway systems in Chinese urban areas, construction workers are being exposed to new risks which are poorly understood and managed. Subway construction projects are large scale and scattered over many construction sites, and involve numerous stakeholders and sophisticated technologies in challenging underground environments. Accident rates are high and have s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 37 publications
0
22
0
2
Order By: Relevance
“…This might be the result of confidentiality terms and conditions of the project contract. However, it is very important to reinforce SIAC research because safety investment positively impacts project performance with reduced accident cost, enhanced productivity and reputation (Zhang et al , 2021).…”
Section: Qualitative Content Analysis and Resultsmentioning
confidence: 99%
“…This might be the result of confidentiality terms and conditions of the project contract. However, it is very important to reinforce SIAC research because safety investment positively impacts project performance with reduced accident cost, enhanced productivity and reputation (Zhang et al , 2021).…”
Section: Qualitative Content Analysis and Resultsmentioning
confidence: 99%
“…On the other hand, Zhang (2018) highlighted the limitations of multi-criteria feasibility evaluations in High-Speed Rail projects in the US. Other research (Zhang et al , 2021; Boadu et al ., 2020) identified the critical factors influencing the safety of Chinese subway construction projects that are directly related to construction projects feasibility.…”
Section: Literature Reviewmentioning
confidence: 89%
“…On the other hand, Zhang (2018) highlighted the limitations of multi-criteria feasibility evaluations in High-Speed Rail projects in the US. Other research (Zhang et al, 2021;Boadu et al, 2020) identified the critical factors influencing the safety of Chinese subway construction projects that are directly related to construction projects feasibility. Fedorova (2019) indicated that feasibility and socio-economic studies of mega infrastructure projects such as rail and metro networks are crucial for sustainable planning of different construction activities of such projects.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the safety level of contractors and subcontractors could directly affect the PSL (Imriyas, 2009). Furthermore, Zhang et al (2020) identified contractor-related factors as a primary variable influencing safety in subway construction projects.…”
Section: Safety Influential Factorsmentioning
confidence: 99%